USE OF INNOVATIVE TECHNOLOGIES IN TEACHING THE TOPICS OF DIVISION IN THE RING OF ALL NUMBERS (Academicia Globe: Inderscience Research, 2022)
The article deals with the divisibility of numbers, which is of interest to mathematicians. Knowing the ability to divide is necessary for everyone to perform the simplest mathematical operations, taking into account complex algebraic expressions and algorithms.